Самооцінка моральних якостей студентів медичного коледжу - Даузе, Г. М. (НТУ "ХПІ", 2018)
В статті наголошується, що розвиток моральних якостей студентів-медиків потребує додаткової уваги та цілеспрямованого формування у навчально-виховному процесі медичного коледжу, оскільки за результатами анкетного опитування студенти-медики вважають, що розвиток їх інтелектуальних якостей зазнає значно більших змін, ніж розвиток моральних під час навчання у коледжі.

The article emphasises that the development of moral qualities of the medical students requires additional attention and purposeful formation in the educational process of the medical college, because according to the results of the questionnaire, medical students consider that the development of their intellectual qualities undergoes significantly more changes than the development of moral qualities during their training in the college.
Self-appraisal of moral qualities of the students of medical college
Keywords: духовність; розвиток духовний; якості інтелектуальні; якості моральні; дисципліни соціально-гуманітарні; spirituality; spiritual development; intellectual qualities; moral qualities; social disciplines; humanitarian disciplines